2m=3(m-10)

Simple and best practice solution for 2m=3(m-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m=3(m-10) equation:


Simplifying
2m = 3(m + -10)

Reorder the terms:
2m = 3(-10 + m)
2m = (-10 * 3 + m * 3)
2m = (-30 + 3m)

Solving
2m = -30 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
2m + -3m = -30 + 3m + -3m

Combine like terms: 2m + -3m = -1m
-1m = -30 + 3m + -3m

Combine like terms: 3m + -3m = 0
-1m = -30 + 0
-1m = -30

Divide each side by '-1'.
m = 30

Simplifying
m = 30

See similar equations:

| 4(y-2)=29 | | 20-z=1 | | 7=7y+2 | | 9-4x=2+6 | | 5(x-2)+2(X+2)=10-2X | | r+3+12=-1 | | 20-2=1 | | 4x+1+2x+6x-10=180 | | 5n-4n+n-2=20 | | 14=0.1x+7 | | 4x-3(y-2)=15ty | | -4/1= | | 6w-1=8w+7 | | 7k=5 | | 17-y=0 | | x+.0507x=1012 | | -12s-30=-7s | | 4a+2p-2a+4p= | | 100+4x=100 | | x^4+8x^3+18x^2-8=0 | | 5c=7y+6 | | 3m+6-2m=-23 | | 3b+5=2b | | -16.7v-1.41=-16.6v | | 7x-9x=5 | | -19.9p+15.01-4p=1.21-10.1p | | 9x+1+3=5x+44 | | 15.70796x=15.70796x+39.25 | | 30X^2+131x+114=0 | | Y=75+12x | | 2-3(x+4)=7 | | X^2+17x+63=0 |

Equations solver categories